2019 Women’s Report Card: An indicator report of Western Australia’s women’s progress - Cassells, Rebecca; Kiely, Daniel; Salazar, Silvia; Seymour, Richard (2019)
The 2019 Women’s Report Card presents factbased information to raise awareness of the status of Western Australian (WA) women. It contributes to the evidence base which underpins actions to address the barriers to women’s progress and promote the benefits of greater gender equity. This report provides reliable information to inform discussion, debate and advocacy. Public, private and community sector organisations can also use this information to develop policies and take action to support women’s progress and to achieve gender equality. The report also fulfils the State Government’s continuing commitment to provide regular updates on the status and progress of WA women. This report recognises that barriers to women’s progress persist and that there is a shared responsibility to improve the status of women and address the barriers to their progress.